Strategic Integration of Tourism, Sports, and Cultural Sectors for Sustainable Regional Development in Malang City - sunarsih, sunarsih (Badan Perencanaan Pembangunan Kota Malang, 2025)
This study investigates the performance transformation of the Office of Youth, Sports, and Tourism (Disporapar) of Malang City in 2023, based on the Performance Accountability Report (LAKIP). The primary aim is to examine the strategic synergy among three core sectors—tourism, sports, and culture—and their contribution to regional development. Employing a qualitative approach with document analysis as the principal method, the findings reveal significant improvements in key performance indicators, with four out of six targets exceeding 100% realization. Notable achievements include a 298.32% increase in youth leadership participation and a 218.85% growth in creative economy actors. These accomplishments reflect robust internal innovation and effective cross-sector collaboration. Beyond presenting quantitative performance metrics, this study offers critical insights into institutional strategies for optimizing regional potential. The integration of measurable, participatory, and outcome-oriented programs across sectors emerges as a vital foundation for building an inclusive and sustainable development ecosystem. In this regard, Disporapar Malang stands as a potential model for transformative local governance—where bureaucracy transcends administrative function to co-create the city’s cultural and social future through synergistic approaches.